Global narratives on unequal outcomes produced by lockdown in Africa: A social science perspective on the “one-size-fits all” COVID-19 response - Grant, Catherine; Sams, Kelley (Frontiers in Public Health, 2023)
Lockdown measures were introduced worldwide to prevent the spread of COVID-19, and several studies showed the positive impacts of these policies in places such as China and Europe. Many African governments also imposed lockdowns at the beginning of the pandemic. These met with mixed reactions; some positive, but others focused on concerns about the consequences of lockdowns. In this paper, we use social listening to examine social media narratives to investigate how people balanced concerns about preventing the spread of COVID-19 with other priorities. Analysing social media conversations is one way of accessing different voices in real time, including those that often go unheard. As Internet access grows and social media becomes more popular in Africa, it provides a different space for engagement, allowing people to connect with opinions outside of their own conceptual frameworks, and disrupting hierarchies of how knowledge is shaped. This article indicates which narratives were favoured by different organisations, stakeholders and the general public and which of these narratives are most dominant in policy discourses. The range of narratives is found to be reflective of the blindness to inequality and social difference of much decision making by policy makers. Thus, contrary to the ‘we are all in this together’ narrative, diseases and public health responses to them clearly discriminate, accentuating long-standing structural inequalities locally, nationally and globally, as well as interplaying with multiple, dynamic, negotiated sources of marginalisation. These and other insights from this paper could play a useful role in understanding and interpreting how social media could be included in pandemic preparedness plans.